Lassa fever clinical course and setting a standard of care for future randomized trials: A protocol for a cohort study of Lassa-infected patients in Nigeria (LASCOPE). Issue 36 (July 2020) - Duvignaud, Alexandre; Jaspard, Marie; Etafo, Ijeoma Chukwudumebi; Serra, Béatrice; Abejegah, Chukwuyem; Gabillard, Delphine; Doutchi, Mahamadou; Alabi, Josephine Funmilola; Adedokun, Moses Adeniyi; Akinpelu, Adewale Oladayo; Oyegunle, Oyebimpe Ope; Etafo, Johnson; et al.
Abstract: Background: Lassa Fever (LF), is a severe viral disease prevalent in Western Africa. It is classified as a priority disease by the World Health Organization (WHO). Ribavirin is the recommended therapy despite weak evidence of its efficacy. Promising therapeutic agents are becoming available for evaluation in human. Before launching therapeutic trials, we need data on the evolution of the disease under the best possible conditions of care. Methods: We have initiated a prospective study in Nigeria to better understand the clinical course and prognostic factors of LF while implementing high quality standardized care. Inclusion criteria are: suspected or confirmed LF and informed consent. Participants are followed 60 days from admission and receive free of charge standardized supportive care and biological monitoring, as well as intravenous ribavirin for those with confirmed LF. Data are collected using standardized case report forms (CRF). Primary and secondary outcomes are fatality and severe morbidity, with special focus on acute kidney dysfunction and pregnancy complications. Factors associated with outcomes will be investigated. Results: The cohort is planned for 3 years. Inclusions started in April 2018 at the Federal Medical Center Owo in Ondo State. A second site will open in Nigeria in 2020 and discussions are underway to open a site in Benin. 150 to 200 new participants are expected per year. Conclusions: This cohort will: provide evidence to standardize LF case management; provide key inputs to design future clinical trials of novel therapeutics; and establish clinical research teams capable of conducting such trials in LF-endemic areas. Study registration: The LASCOPE study was registered on ClinicalTrial.gov (NCT03655561).